Industrial Training Report: Tuanku Bainun Library Universiti Pendidikan Sultan Idris / Rosfazilah Mohd Rosli - Mohd Rosli, Rosfazilah (Faculty of Information Management, 2018)
The purpose of this documentation is to report the activities during Industrial Training for five months in Tuanku Bainun Library (PTB). The reports include daily task assigned to the trainee by each department such as customer and collection, cataloging, acquicition, academic support, administration and library automation and conduct the activities. This report has included about special project which is make a research about services library through perception user about Reader Advisory service. The purpose for this special project is to know about feedback the user perception of Reader Advisory service provided in the library such as OPAC search and source of information in the database, research consultation, interlibrary loan, student status and indicator location material.